Serving God with Style: Unleashing Servant Potential - Williams, Ronald C. (Rowman & Littlefield Publishers, 2002)
Every church is driven by its faith in God, and seeks to grow that faith by guiding its members toward fruitful ministry. But in the face of accelerating change, congregations often find themselves spinning their wheels, exerting great amounts of energy to little effect: the faith is willing, but, faced with uncertainties, the results are weak. How can faith be transformed into productive ministry? Ron Williams, a recognized expert in ministry organization and development, has observed that as individuals better understand their own behavioral tendencies when dealing with uncertainties and exercising their "faith styles," the more intentional - and thus, more productive - they will be. To that end, Williams has created the "Servant Resource Faith-Style Inventory" that congregations can use as a tool in training ministry volunteers, developing ministry teams, educating ministry leaders, developing Christ-centered work-ethic training, empowering Christians in the secular workplace, and other ministry development interventions. Deeply informed by evangelical faith yet useful in a broad variety of ministry settings and traditions, the Inventory provides a useful instrument for congregations which have found that other self-evaluation tools borrowed from secular sources do not meet the particular needs of Christian churches. Dynamic and personal in tone, and faith-based in the deepest sense, Serving God with Style will help every congregation enhance ministry effectiveness for the glory of God.